Design and Subject Characteristics in the Federally-Funded Citalopram Trial in Children with Pervasive Developmental Disorders - Scahill, Lawrence; McCracken, James T.; Bearss, Karen; Robinson, Fay; Hollander, Eric; King, Bryan; Bregman, Joel; Sikich, Lin; Dukes, Kimberly; Sullivan, Lisa; Anagnostou, Evdokia; Donnelly, Craig; et al. (Journal of autism and developmental disorders, 2012)
The Studies to Advance Autism Research and Treatment Network conducted a randomized trial with citalopram in children with Pervasive developmental disorders (PDDs). We present the rationale, design and sample characteristics of the citalopram trial. Subjects (128 boys, 21 girls) had a mean age of 9.3 (±3.12) years; 132 (88.6%) were diagnosed with autistic disorder (4.7% with Asperger’s Disorder; 6.7% with PDD-not otherwise specified). Less than half of the subjects were intellectually disabled; 117 (78.5%) were rated Moderate or Marked on the Clinical Global Impression for Severity. Study measures were similar to previous Research Units on Pediatric Psychopharmacology trials. Subjects in this trial were slightly older and more likely to have complaints of repetitive behavior than participants in RUPP trials.